Sustainable Urban Drainage Systems: Global Review of Environmental Benefits and Implementation Challenges - Paudel, Roshan; Bhandari, Soniya; Shrestha, Dina; Bhattarai, Shraddha; Bhandari, Sirish; Giri, Suja; Khanal, Avishek; Khanal, Ashish (Journal of Sustainability and Environmental Management, 2024)
Urbanisation has led to numerous challenges in terms of stormwater management and environmental impact. Sustainable Urban Drainage Systems (SUDS) have emerged as a promising approach to mitigate these challenges by mimicking natural processes and providing environmentally sound water disposal systems. This review paper provides a comprehensive overview of the status of SUDS on a global scale, focusing on their development, challenges, and environmental benefits. This review paper discusses various SUDS techniques, including permeable paving, green infrastructure, and detention ponds, and highlights their effectiveness in reducing stormwater runoff, improving water quality, and enhancing ecological services. The paper also identifies the challenges faced in implementing SUDS, including technical complexity, lack of common platforms for SUDS models, limited operational experience, and institutional barriers. Additionally, the paper presents potential solutions to overcome these challenges, such as promoting research and development, providing training and capacity-building programs, and establishing guidelines and standards for SUDS design. The findings and recommendations presented in this paper contribute to the development of sustainable urban environments and the enhancement of overall environmental conditions.